DISPENSASI NIKAH PADA PENETAPAN NOMOR 0230/Pdt.P/2018/PA.Kab.Kdr PASCA LAHIRNYA UNDANG-UNDANG NOMOR 16 TAHUN 2019 - Daffa Arrafi Adi Pratama; Mia Hadiati (Fakultas Hukum Universitas Tarumanagara, 2022)
In the past, marriage at a young age was still considered commonplace, but over time it has changednot a few people who oppose marriage at an early age, for example in the determination of the KediriRegency Religious Court Number 0230/Pdt.P/2018/PA.Kab.Kdr there are application for dispensationof marriage submitted by the Petitioner, whereas the Petitioner in his application letter stated that thePetitioner has a nephew who is 16 years old, the Petitioner will soon marry of the niece of thePetitioner to his future wife who is 15 years old. The problem in writing this thesis is how to apply fora marriage dispensation permit after the birth of Law Number 16 of 2019? and how is the judge'sconsideration in determining the marriage dispensation in the determination of Number0230/Pdt.P/2018/PA.Kab.Kdr.?. Marriage dispensation is a decision that can provide freedom fromseveral rules, which are given by the Religious Courts to be able to carry out marriages, for men andwomen who have not yet reached the minimum age limit set by Law No. the marriage can be carriedout and ratified by the KUA (religious af airs of ice). In conclusion, the granting of a marriagedispensation permit by the Religious Court of Kediri Regency, the author feels that there are severalregulations that have not been included as a consideration in the determination apart from beingbased on Law Number 16 of 2019.